A systematic study of glycopeptide esterification for the semi‐quantitative determination of sialylation in antibodies. (26th August 2015) - Gomes de Oliveira, Andrey Giovanni; Roy, Rini; Raymond, Céline; Bodnar, Edward D.; Tayi, Venkata S.; Butler, Michael; Durocher, Yves; Perreault, Hélène
<x xml:space="preserve">Abstract</x> Rationale In the expression of recombinant proteins, an important parameter to control or influence is their level of sialylation. Matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) mass spectrometric (MS) methods tend to either underestimate (positive mode) or overestimate (negative mode) the content of sialylated vs. neutral glycans in glycoproteins. Esterification methods have been developed for free sialylated glycans and sialylated Asn‐glycans, allowing these acidic groups to ionize with the same efficiency as neutral sugars. Methods Here we describe a method which modifies glycopeptides by esterification. This simple procedure is applied to glycopeptides isolated from tryptic digests of monoclonal antibodies (mAbs), some highly sialylated. To better understand the effect of esterification on the peptide backbone, synthetic EEQYNSTYR was esterified and studied by tandem mass spectrometry (MS/MS). Acetamidation of EEQYNSTYR was also studied as some mAb samples had been overalkylated prior to tryptic digestion. Results As a general trend, ethyl‐esterification or lactonization is observed for each sialic acid on glycoforms of EEQYNSTYR (the N‐glycosylated tryptic peptide of IgG Fc), depending on the branching position of the sialic acid (α2, 3 or α2, 6). Esterification also affects the carboxyl groups in the peptide, including the C‐terminal COOH. Conclusions For antibody analysis, MALDI‐MS ion abundances give a better semi‐quantitative estimate of sialylation levels for esterified than for unreacted glycopeptides. The method is simple to use and helps to differentiate the branching patterns of sialic acids in antibodies. Copyright © 2015 John Wiley & Sons, Ltd.